Characteristics of shallow and mesophotic environments of the Pemba Channel, Tanzania: Implications for management and conservation. (1st February 2021) - Osuka, Kennedy E.; McClean, Colin; Stewart, Bryce D.; Bett, Brian J.; Le Bas, Tim; Howe, John; Abernerthy, Colin; Yahya, Saleh; Obura, David; Samoilys, Melita
Abstract: Information on the spatial distribution of habitats and vulnerable species is important for conservation planning. In particular, detailed knowledge on connectivity of marine ecosystems in relation to depth and seafloor characteristics is crucial for any proposed conservation and management actions. Yet, the bulk of the seafloor remains under-sampled, unstudied and unmapped, thereby limiting our understanding of connections between shallow and deep-water communities. Recent studies on mesophotic coral ecosystems (MCEs) have highlighted the Western Indian Ocean as a particularly understudied marine region. Here we utilise an autonomous underwater vehicle (AUV) to collect in-situ temperature, oxygen concentration, bathymetry, acoustic backscatter and photographic data on benthic communities from shallow (<30 m) and mesophotic (30–150 m) depths at selected sites in the Greater Pemba Channel, Tanzania. Further, we use generalised additive models (GAMs) to determine useful predictors of substratum (hard and sand) and benthic community type (coral, turf algae, fleshy algae, fish). Our results revealed the presence of a complex seafloor characterised by pockmarks, steep slopes, submarine walls, and large boulders. Photographs confirmed the presence of MCE composed of corals, algae and fishes on the eastern margins of the Pemba Channel. The GAMs on the presence and absence of benthic community explained 35%–91% of the deviance in fish and fleshy algae assemblages, respectively. Key predictors of the distribution of hard substrata and the coral reef communities were depth, showing the upper boundary of MCEs present at 30–40 m, and seafloor slope that showed more occurrences on steep slopes. The upper 100 m of water column had stable temperatures (25–26 °C) and oxygen concentrations (220–235 μmol/l). We noted the presence of submarine walls, steeply inclined bedrock, which appeared to support a highly bio-diverse community that may be worthy of particular conservation measures. Our results also highlight the capability of using marine robotics, particularly autonomous vehicles, to fill the knowledge gap for areas not readily accessible by divers or with surface vessels, and their potential application for the initial survey and subsequent monitoring of Marine Protected Areas. Graphical abstract: Image 1 Highlights: Demonstrates autonomous underwater vehicle use in tropical reef ecosystems. Assesses occurrence of mesophotic coral ecosystems (MCEs) in the western Indian Ocean. Develops models of habitat and community type presence from environmental variables. Observes diverse coral systems on steep slope or walls and suggests their need for protection. Considers the further use of autonomous underwater vehicles in conservation efforts.